Mapping Potential And Development Strategies Of Marine Tourism In The Morotai National Tourism Strategic Area - Erland Mouw; Nina Karlina; Ida Widianingsih; Heru Nurasa (Aliansi, 2022)
The potential as well as the strategy of development of tourism in the National Tourism Strategic Area Morotai be important for mapping and analyzing the strategies that have been undertaken by the government until recently. The purpose of this paper is the analysis of the potential and the strategy of development of tourism in the National Tourism Strategic Area Morotai. Mapping the potential of marine tourism, beginning with a survey of the field, find the problems, then learn the theory in accordance with the problem. The method used a Mixed Method by taking the documentation data and primary data through In-Depth Interview guests, private, group of society, which is scattered in four areas of development, namely (1) Wayabula; (2) Daruba; (3) Bere-bere and Sopi. Mapping the tourism potential of the Island of Morotai is divided in 3 (three) types of the city, namely marine tourism 22 the city, its history 8 the city; and tour the cave and the waterfall is 9 km from. As for the strategy of development of tourism the Island of Morotai directed at : (a). The strategy of development of tourism; (b). Product Development strategy and Attractions; (c). Development strategy of Amenities available at the National Tourism Strategic Area Morotai; (d). The strategy of the development of accessibility associated with the development of National Tourism Strategic Area Morotai; and (e). Development strategy of promotion and marketing. The recommendation is that the government District of the Island of Morotai should seriously implement the development strategy of marine tourism. In addition, the development of products and places, the development of ksesibilitas, the development of ammenities, and the promotion of marine tourism should be further optimized.